The Moderating Effect Of Gender On The Relationship Between Service Quality and Student Satisfaction Using A Hesqual Model: Evidence From A Private University In East Borneo - Haryadi Jaka Susila; Rr. Iramani (Journal of Business & Banking, 2025)
ABSTRACT Higher education institutions face challenges in providing services to meet student expectations. This study aims to examine the impact of service quality on student satisfaction using the HESQUAL (Higher Education Service Quality) model. Sampling was used with random sampling technique, involving 290 respondents. Data analysis was conducted with SEM-PLS. The results showed that administrative services, physical facilities, and teaching quality had a significant positive impact on student satisfaction. However, academic services related to the Academic Information System (SIAKAD) do not have a significant impact on student satisfaction. The results of this study imply that to increase student satisfaction, education service providers should optimize administrative procedures, better facility maintenance, and excellent lecturer services.